Challenges at the interface of data analysis, computer science, and optimization : Proceedings of the 34th Annual Conference of the Gesellschaft for Klassifikation e. V., Karlsruhe, July 21 - 23, 2010 - Geyer-Schulz, Andreas; Schmidt-Thieme, Lars; Kunze, Jonas; Gaul, Wolfgang A. (Studies in Classification, Data Analysis, and Knowledge Organization, 2012)
This volume provides approaches and solutions to challenging problems occurring at the interface of research fields such as data analysis, computer science, operations research, and statistics. It includes theoretically oriented contributions as well as papers from various application areas, where knowledge from different research directions is needed to find an adequate analysis and interpretation of the observed data that match optimally the underlying practical situations. Beside traditional classification research, the book focuses also on current interests in fields such as the analysis of network data, graphs, and social relationships as well as on statistical musicology.